2018
DOI: 10.1097/ceh.0000000000000195
|View full text |Cite
|
Sign up to set email alerts
|

Adapting the Consolidated Framework for Implementation Research to Create Organizational Readiness and Implementation Tools for Project ECHO

Abstract: The Project Extension for Community Healthcare Outcomes (ECHO) model expands primary care provider (PCP) capacity to manage complex diseases by sharing knowledge, disseminating best practices, and building a community of practice. The model has expanded rapidly, with over 140 ECHO projects currently established globally. We have used validated implementation frameworks, such as Damschroder's (2009) Consolidated Framework for Implementation Research (CFIR) and Proctor's (2011) taxonomy of implementation outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 26 publications
(41 reference statements)
2
39
0
Order By: Relevance
“…Technology-delivered care can be helpful in scaling interventions for rural adults with obesity residing in remote areas Policymakers can enhance reimbursement and incentives to promote telemedicine-delivered care to adults Enhancing patient/staff engagement and culture can overcome organizational stress and enhance reach of the intervention the Consolidated Framework for Implementation Research (CFIR) and RE-AIM [5]. These frameworks have previously been applied in the context of telemedicine and have found that patient and leadership engagement, comfort levels with the technology, and a need to have similar efficacy and workflows to in-person visits were important factors [6][7][8]. As such, the purpose of this analysis was to apply these established implementation frameworks to refine our intervention for a future, large-scale trial that could ensure its long-term success and program sustainability in rural areas.…”
Section: Contributions To the Literaturementioning
confidence: 99%
“…Technology-delivered care can be helpful in scaling interventions for rural adults with obesity residing in remote areas Policymakers can enhance reimbursement and incentives to promote telemedicine-delivered care to adults Enhancing patient/staff engagement and culture can overcome organizational stress and enhance reach of the intervention the Consolidated Framework for Implementation Research (CFIR) and RE-AIM [5]. These frameworks have previously been applied in the context of telemedicine and have found that patient and leadership engagement, comfort levels with the technology, and a need to have similar efficacy and workflows to in-person visits were important factors [6][7][8]. As such, the purpose of this analysis was to apply these established implementation frameworks to refine our intervention for a future, large-scale trial that could ensure its long-term success and program sustainability in rural areas.…”
Section: Contributions To the Literaturementioning
confidence: 99%
“…In this paper, we examine the feasibility, acceptability, and impact of a national Project ECHO training program created specifically for CHWs to enhance their competency and improve their ability to address patients' SDOH. Prior implementation research related to Project ECHO has identified feasibility and acceptability as key components to ensuring implementation success [20], yet it is unknown to what extent CHWs will choose to participate in and have their learning needs met by a national ECHO with a broader curriculum. In addition to feasibility and acceptability, we also assess impact so as to understand immediate outcomes related to the intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the physical distance between the community of interest and the research team, the use of video and telecommunication is key in delivering this intervention. Previous research has adapted the CFIR to assess readiness for and suitability of a tele-mentoring platform, the Project Extension for Community Healthcare Outcomes (ECHO), and created ECHO-specific organizational readiness questions and a process guide for implementation [ 65 ]. Using the CFIR as a guide for our project may also yield information that can be adapted and utilized as guidelines for other interventions involving OUD-specific remote education.…”
Section: Discussionmentioning
confidence: 99%